Correlations of anthropometric and body composition variables with the performance of young elite weightlifters - Siahkouhian, M.; Hedayatneja, M. (Journal of Human Kinetics, 2010)
The aim of this study was to evaluate the correlations of anthropometric and body composition variables with the performance (i.e., snatch; clean & jerk; front squat; back squat) of Iranian elite weightlifters. Fortytwo subjects (mean ± SD of age 16.21 ± 3.22 years) volunteered to participate in the study. All subjects competed at the Iranian National Championship. Anthropometric and body composition variables, including height, sitting height, cormic index, lean body mass (LBM), body mass index (BMI), modified BMI (by the cormic index), %fat, shoulder circumference, chest circumference, WHR (wrist to hip ratio), as well as performance of weightlifters (i.e., snatch; clean & jerk; front squat; back squat) were measured. Results showed that the snatch and clean & jerk records significantly correlated with height, sitting height, weight, shoulder and chest circumference, LBM, BMI; whereas we showed negative correlations between the snatch and clean & jerk records with the %fat as well as WHR values. Results also showed that the snatch and clean & jerk records significantly correlated with body mass index (BMI) (r= 0.357, and r= 0.374; p<0.05); however there was no relationship between snatch and clean & jerk records and the modified body mass index (MBMI). According to the results, it was concluded that there was strong correlations existing between weightlifter performance and the anthropometric and body composition variables. Also, it is recommended that the cormic index (CI) is a corrective factor for BMI values.